Chambers spell it your self! - Hawker(3, (BG Ts (Ljubljana Chambers Hawaker, 2007)
Spell it yourself ! is a consistently bestselling title that lists thousands of words children might want to spell, followed by their different endings. so not only does the book make it quick and easy to find a spelling, it also build up knowledge of word families and how to spell words from their root forms
The bestselling system for learning spelling
12
Keywords: English Language; Spelling reform